The Logical Discipline of Normative Argumentation. Some considerations on the axiological status of speech acts - Wawrzyniak, Jan (Investigationes Linguisticae, 2006)
This paper is intended to promote a way of is-ought derivation, rooted in neonaturalistic solutions which were worked out within the scope of both the ontology of values and meta-ethical applications of 20th Century linguistic philosophy. Normative, especially in the sphere of morality, reasoning is supposed to be the most significant component of the structure of social communication. The common practices of normative persuasion employ a variety of modes of argumentation, such as the usage of evaluations, norms, imperatives, performative utterances, prescriptions, and optatives. There is a wide range of kinds of emotive pressure produced by speech acts, behind which some intentions of perlocutionary effects are hidden, and which all have methodologically differentiated status. Therefore, the ability to recognize some tricks employed in such practices, as well as the qualified faculty of argumentation for and validation of one‟s own moral convictions seems to be an indispensable component of a subject‟s high cultural competency. The moral responsibility for social states-of-affairs generated by speech acts requires such competency. The neonaturalistic approach – itself representing cognitive meta-ethics and recognizing the pragmatic functions of speech acts as a social phenomenon – proposes a philosophical alternative to the cage of formalized languages (like various systems of deontic logic) for normative reasoning in order to find real, verifiable – not necessarily of contractual origin – value-referred premises for the inference of socially applied judgments of duty. The distinction between logical validation and moral (value-referred) justification of imperatives is emphasized at the same time. On this account certain philosophical interpretations of the categories of “fact”, “value” and “personal agent of valuation and cognition” are carried out and an example of is-ought inference is presented.